2000
DOI: 10.1038/sj.jim.7000105
|View full text |Cite
|
Sign up to set email alerts
|

The production of mixed cultures containing strains of Lactococcus lactis, Leuconostoc cremoris and Lactobacillus rhamnosus , on commercial starter media

Abstract: Mixed starters containing Lactococcus lactis, Leuconostoc cremoris and Lactobacillus rhamnosus strains were produced on commercial starter media (MB Complete, Thermolac, Marlac), as well as on milk. With the exception of Marlac, the starters were cultured under pH control. The effect of media and incubation temperature (22 or 32 degrees C) on population ratios, on specific acidifying activities (SAA) of the cultures as well as on their ability to produce aroma compounds in milk was studied. The starters had hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 0 publications
5
18
2
1
Order By: Relevance
“…A balanced growth of species occurs during incubation between 21 C and 25 C. At temperature above 25 C, the ratio is skewed toward the metabolically more active Lc. lactis, which grows at a faster rate at higher temperature (between 25 C and 32 C) relative to the Leuconostoc (Vedamuthu, 1994; Liu et al, 1997;Baron, Roy, & Vuillemard, 2000;Barrette et al, 2000).…”
Section: Growth and Metabolism Of Leuconostoc In Mixed Strain Culturesmentioning
confidence: 98%
“…A balanced growth of species occurs during incubation between 21 C and 25 C. At temperature above 25 C, the ratio is skewed toward the metabolically more active Lc. lactis, which grows at a faster rate at higher temperature (between 25 C and 32 C) relative to the Leuconostoc (Vedamuthu, 1994; Liu et al, 1997;Baron, Roy, & Vuillemard, 2000;Barrette et al, 2000).…”
Section: Growth and Metabolism Of Leuconostoc In Mixed Strain Culturesmentioning
confidence: 98%
“…Diacetyl and acetaldehyde were analysed by gas chromatography as described by Barrette et al (2000).…”
Section: Aroma Compoundsmentioning
confidence: 99%
“…cremoris strains, and mixed cultures containing aroma-producing strains are traditionally grown in milk without pH control (Harvey, 1965;Hugenholtz, 1986;Thu- nell, 1988). In addition, it was shown that Leuconostoc cremoris and Lactobacillus rhamnosus cultures do not compete well with the lactococci in commercial starter media used under external pH control (Barrette, Champagne, Roy, & Rodrigue, 2000). Therefore, preparing mixed cultures under pH control is not an easy task.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At temperatures above 25°C, L. lactis grows substantially faster than Leuconostoc sp. [40], whereas at temperatures between 21°C and 25°C a more balanced growth of both genera is observed [39]. During the initial phase of cheese manufacturing, Le.…”
Section: Introductionmentioning
confidence: 99%